2015
DOI: 10.1109/temc.2015.2414356
|View full text |Cite
|
Sign up to set email alerts
|

Field-to-Wire Coupling Model for the Common Mode in Random Bundles of Twisted-Wire Pairs

Abstract: magnetic modeling still represents a challenging problem as concerns prediction of crosstalk and field-to-wire coupling. Indeed, deterministic modeling based on the representation of specific and arbitrary cable geometries would be an exercise in futility, due to the high sensitivity of the induced noise to different random configurations of the bundle. Consequently, statistical models are more suited, since they are based on the description of model parameters and results in terms of random variables and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 20 publications
1
54
1
Order By: Relevance
“…It is observed that good agreement is achieved between our model and FEKO results, although there are some deviations at low frequencies in the broad-side case. These deviations occurred because the currents are extremely small at very low frequencies, and they are very sensitive to any slight change of geometrical parameters of the MTB-TWP, with the similar phenomena shown in the previous studies, 8,33 respectively (Figure 8).…”
Section: Model Validationsupporting
confidence: 83%
See 1 more Smart Citation
“…It is observed that good agreement is achieved between our model and FEKO results, although there are some deviations at low frequencies in the broad-side case. These deviations occurred because the currents are extremely small at very low frequencies, and they are very sensitive to any slight change of geometrical parameters of the MTB-TWP, with the similar phenomena shown in the previous studies, 8,33 respectively (Figure 8).…”
Section: Model Validationsupporting
confidence: 83%
“…The extension of the equivalent cable bundle method for modeling crosstalk in complex cable bundles was done in the previous study . More recently, Pignari et al have carried out very effective studies on modeling field‐to‐wire coupling in bundles of TWP with different geometries, respectively. Because of the geometrical feature of TWP as well as TWP bundles, both analytical and numerical methods can be implemented for predicting their input‐output responses or crosstalk among them, while analytical or semianalytical approaches can save much time for simulating many TWPs in comparison with the commercial software FEKO…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the first structure under analysis represents a harness composed of an arbitrary number of wires and interconnected to terminal units. Since radiated susceptibility is characterized by a dominant CM coupling mechanism [8], in Fig. 1(a) the multi-wire harness is reduced to a single equivalent wire describing the propagation of CM voltages/currents [11].…”
Section: A Structures Under Analysismentioning
confidence: 99%
“…Statistical techniques recently gained increasing attention from the Electromagnetic Compatibility (EMC) community, owing to the need to handle systems in which some parameters may randomly vary either due to manufacturing tolerances or due to uncertainty in the knowledge of their exact value. This is, for instance, the case of complex wiring harnesses, whose geometrical characteristics, such as precise position of wires in the bundle, are often hard to be controlled [1][2][3][4]. Since these random variations may significantly impact EMC performance, modeling and propagating the uncertainty associated with these parameters become of paramount importance in order to provide a statistical characterization (in terms of statistical moments) of relevant electrical quantities.…”
Section: Introductionmentioning
confidence: 99%